Comparative Effectiveness of Radiofrequency Ablation vs. Surgical Resection for Patients With Solitary Hepatocellular Carcinoma Smaller Than 5 cm - Zheng, Lei; Zhang, Chi-Hao; Lin, Jia-Yun; Song, Chen-Lu; Qi, Xiao-Liang; Luo, Meng (Frontiers in Oncology, 2020)
Background: This study aims to compare survival outcome after receiving radiofrequency ablation (RFA) and surgical resection (SR) for solitary hepatocellular carcinoma (HCC) with size large as 5 cm. Methods: The SEER database was queried for patients with HCC tumors who were treated with RFA or SR between 2004 and 2015. Univariate and multivariate Cox analysis was used to assess the influence of potential variables on the patients' outcome. Additionally, propensity score matching (PSM) and multiple imputations (MI) were used as sensitivity analyses. Results: Of 1,985 cases, 934 patients received RFA treatment, while the rest underwent surgical resection. The patients in the RFA group had poorer overall survival (OS) and cancer-specific survival (CSS) than those in the SR group regardless of the tumor size before matching and MI. By using PSM analysis at a 1:1 ratio, 1,302 cases were paired and we have found that SR had a positive impact on OS and CSS of patients with tumors measuring from 3.1 to 5 cm. However, when the tumor size was <3 cm, patients undergoing SR had similar survival benefit with those after RFA. The above results were confirmed after performing PSM analysis at a 1:2 and 1:3 ratio. Conclusion: By applying several effective sensitivity analyses, we demonstrated that OS and CSS were similar between the patients with tumors smaller than 3 cm receiving RFA and SR. But SR may be a superior treatment option with better long-term outcome than RFA in patients with tumor measuring 3.1–5 cm.